(untitled) (Minerva, 2019)
The present article treats two points about the civil war that faced Caesar and Pompey in Thessaly. On the one hand, Caesar’s passage (Caes. BCiv. 3,35,2) about the division in factions of this region and their possible cause. For other, the possibility of coinage on the part of the characters mentioned by Caesar during this conflict.